DDX24 spatiotemporally orchestrates VEGF and Wnt signaling during developmental angiogenesis - Fangbin Chen; Zhaohua Deng; Xiaoming Wang; Yuxuan Liu; Kaichen Zhao; Yue Zhang; Simeng He; Rensen Ran; Yingying Dong; Shuang Guo; Yitong Zhou; Bin Zhou; et al. (Proceedings of the National Academy of Sciences, 2025)
Vascular development is a precisely controlled process, yet how it is spatiotemporally orchestrated remains enigmatic. We previously identified DEAD-box RNA helicase 24 (DDX24) as a pathogenic gene for multiorgan vascular anomalies. Here, we show that DDX24 is expressed in the endothelium during embryonic angiogenesis in zebrafish. DDX24 deficiency causes intersegmental vessel hyperbranching in the trunk, but inhibits central artery angiogenesis in the brain. Mechanistically, DDX24 deficiency enhances VEGFR2 expression by direct binding to its mRNA in nonbrain endothelial cells (ECs), while suppressing GPR124/RECK-mediated Wnt signaling in brain ECs. Additionally, spatial transcriptome analysis profiles DDX24-mediated crosstalk between ECs and neighboring cells. Finally, pharmacological targeting of these two pathways in a temporal manner can rescue the phenotypes induced by DDX24 deficiency. Overall, our findings highlight an essential role for DDX24 in the spatiotemporal regulation of developmental angiogenesis.